Recuperación de cartera vencida del gobierno autónomo descentralizado del cantón montalvo periodo 2021 y 2022. - García Alvear, Adrián Leonel (2024)
Among their functions, the Decentralized Autonomous Governments have to promote their own income such as taxes, fees and contributions, which are to finance investment projects or cover current expenses. Private or public entities, if the values issued for taxes are not collected in full, these will have an impact on an increase in the delinquency rate that will be reflected in the accounts receivable called PORTFOLIO MATURITY, if the strategies or procedures such as coercive processes of collection is not met or the expected effectiveness is achieved, such values will continue to inflate period after fiscal period. The aforementioned in the years 2021 -2022 has occurred in GAD MONTALVO since the item “Recovery of overdue portfolio” has an initial allocation of $244,468.04 and manages to collect $220,765.84, having a difference of $-23,702.20. In other words, it managed to collect 90.30% of the total that it intended to receive in that year. When comparing the collection of the “Recovery of past due portfolio” item in 2021 and 2022, there is a difference of $-44,168.06 in relation to the previous year, that is, it managed to collect less and represented in percentage value is -20.01%. In this regard, it is proposed that this entity designate specific personnel with knowledge in coercive processes so that the measures or decision-making are the most suitable in such a way that it has an impact on the reduction of the receivable portfolio and the resources obtained provide sustainability and liquidity to the entity. institution.